THE POLITICAL ELITES OF THE NORTH CAUCASUS REPUBLICS IN THE CONTEXT OF RELATIONS BETWEEN THE MODERN AUTHORITIES AND SOCIETY - Yulia Viktorovna Usova; Boris Georgievich Koybaev (Современная наука и инновации, 2022)
The article deals with relationship problems of modern government and society on the example of the North Caucasian Republics; the issues of formation, functioning and quality features of regional political elites, that is the most important factor in ensuring the vital activity of any power system are explored